Case report: Increased troponin level in 125 children during COVID-19 - Di Filippo, Paola; David, Daniela; Attanasi, Marina; Rossi, Nadia; Chiarelli, Francesco (Frontiers in Pediatrics, 2023)
Introduction: Increase in cardiac biomarkers during Coronavirus disease 2019 (COVID-19) was frequent regardless of the presence of myocarditis and multisystem inflammatory syndrome in children (MIS-C). Several studies described MIS-C, but few papers evaluated cardiac manifestations in children with SARS-CoV-2 infection without MIS-C and investigated the role of troponin in absence of electrocardiogram (ECG) and echocardiographic alterations. The aim of this case series is to describe the cardiac manifestations during COVID-19 in children, trying to explain the meaning of laboratory findings during COVID-19, especially of increased troponin. Materials and Methods: We conducted a retrospective case series of children aged <18 years admitted at the Department of Pediatrics, University of Chieti, for SARS-CoV-2 infection between 1st March 2020 and 31th July 2022. All patients with documented SARS-CoV-2 infection underwent a laboratory evaluation at admission. Children with increased troponin I and/or BNP underwent electrocardiographic and echocardiographic exams. Results: 125 children were admitted for SARS-CoV-2 infection to our Department of Pediatrics, of whom 17 (13,6% of cases) with different patterns of cardiac involvement. Specifically, 5 subjects (4.0% of admitted children) were diagnosed as MIS-C and 12 children (9,6%) manifested a cardiac involvement in terms of increased troponin with or without ECG and echocardiography anomalies. Troponin, C-reactive protein, procalcitonin and BNP values resulted higher in patients with MIS-C compared to patients without MIS-C. Furthermore, patients with MIS-C had higher neutrophils and lower lymphocytes compared to patients without MIS-C. ECG abnormalities were found in 4/5 patients with MIS-C and in 2/12 patients without MIS-C. Echocardiographic anomalies were found in all patients with MIS-C, especially in terms of valve regurgitation and ejection fraction reduction and in 2/12 patients without MIS-C, especially in terms of pericardial effusion. Despite high troponin levels, children presented a favorable clinical evolution. Conclusion: the increase in troponin level in children with COVID-19 could also be due to respiratory causes or a massive inflammatory state. In our case series, patients with increased troponin associated to COVID-19 presented a favorable clinical course with clinical and laboratory remission almost always within 7 days.